THE MAIN DIRECTIONS OF ANALYSIS OF GENDER LINGUISTICS - Haqberdiyeva Gulrux Tolibovna (EPRA International Journal of Research and Development (IJRD), 2022)
This article describes the necessary ideas on the main directions of the analysis of gender linguistics and the results of observations of well-known linguists.